2009
DOI: 10.1007/s00122-009-1239-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a major QTL conferring crown rot resistance in hexaploid wheat

Abstract: Crown rot (CR), caused by various Fusarium species, is a chronic wheat disease in Australia. As part of our objective of improving the efficiency of breeding CR resistant wheat varieties, we have been searching for novel sources of resistance. This paper reports on the genetic control of one of these newly identified resistant genotypes, 'CSCR6'. A population derived from a cross between CSCR6 and an Australian variety 'Lang' was analyzed using two Fusarium isolates belonging to two different species, one Fusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 23 publications
5
89
1
5
Order By: Relevance
“…CR resistance of the two novel sources in wheat we analyzed was each controlled by a major 3BL locus Ma et al 2010). The segregating populations used so far do not allow us to clarify if the same gene is involved in these two resistance sources.…”
Section: Discussionmentioning
confidence: 99%
“…CR resistance of the two novel sources in wheat we analyzed was each controlled by a major 3BL locus Ma et al 2010). The segregating populations used so far do not allow us to clarify if the same gene is involved in these two resistance sources.…”
Section: Discussionmentioning
confidence: 99%
“…They were found on five different chromosomes. However, recent studies have identified a major QTL on the long arm of chromosome 3B for CR resistance in three different wheat genotypes (Li et al, 2010a;Ma et al, 2010, Bovill et al, 2010. The magnitude of the 3B CR QTL identified in these genotypes explained up to 34.6%, 40.2%, and 46.2% of the phenotypic variance with detection in each of the trials in the three independent studies.…”
Section: Introductionmentioning
confidence: 93%
“…A total of 28 publically available PCR-based markers were used in this study and nine polymorphic ones (in red) were filled into the region where the 3B QTL harboured Figure 2 The wheat 3B crown rot QTL identified in the resistant variety Ernie (Li et al, 2010) was remapped using a linkage map constructed using only PCR-based markers. The CR-associated markers are applied in validation study and have the potential value to be used in breeding for CR resistance in wheat Figure 3 The barley 3H crown rot QTL identified in the resistant variety TX9425 (Li et al, 2009) was remapped using a linkage map constructed using only PCR-based markers.…”
Section: Validation Of 3b Qtlmentioning
confidence: 99%
See 2 more Smart Citations